New accelerating cosmology without dark energy: the particle creation approach and the reduced relativistic gas - Lima, P. W. R.; Lima, J. A. S.; Jesus, J. F. [UNESP] (Springer Nature, 2025)
The standard procedure to explain the accelerated expansion of the Universe is to assume the existence of an exotic component with negative pressure, generically called dark energy. Here, we propose a new accelerating flat cosmology without dark energy, driven by the negative creation pressure of a reduced relativistic gas (RRG). When the hybrid dark matter of the RRG is identified with cold dark matter, it describes the so-called CCDM cosmology whose dynamics is equivalent to the standard Λ$$\Lambda $$CDM model at both the background and perturbative levels (linear and nonlinear). This effect is quantified by the creation parameter α$$\alpha $$. However, when the pressure from the RRG slightly changes the dynamics of the universe, as measured by a parameter b, the model departs slightly from the standard Λ$$\Lambda $$CDM cosmology. Therefore, this two-parametric model (α,b$$\alpha , b$$) describes a new scenario whose dynamics is different but close to the late-time scenarios predicted by CCDM and Λ$$\Lambda $$CDM models. The free parameters of the RRG model with creation are constrained based on SNe Ia data (Pantheon+SH0ES) and also using H(z) from cosmic clocks. In principle, this mild distinction in comparison with both CCDM or Λ$$\Lambda $$CDM may help alleviate some cosmological problems plaguing the current standard cosmology.